Transnational Authoritative Parenting and Academic Motivation: A Self-Determination Theory Perspective on Children of Migrant Workers - Luthfi Atmasari; Nisa Fitriani; Misbahul Munir (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Academic motivation is an important element in student success in an educational context. The absence of parents is known to have an important role in reducing academic motivation. However, based on theoretical studies and previous research, it is suspected that parental parenting, especially authoritative, is able to increase students' learning motivation even though they do not literally support them. The aim of this research is to determine the influence of the authoritative parenting style of parents who work as migrant workers on the academic motivation of MTsN 3 Tulungagung students. The research method that is relevant to the objectives of this research is the quantitative research method with simple regression tests. The research instruments used were the Parenting Styles and Dimensions Questionnaire (PSDQ) and The Academic Motivation Scale (AMS). Meanwhile, the sample in this research was class VIII students at MTsN 3 Tulungagung with predetermined criteria. Statistical testing confirmed a significant positive effect of authoritative parenting on academic motivation (p < 0.05; t = 4.83), with the regression model accounting for 28% of the variance in motivation levels. These findings imply that physical distance does not necessarily diminish parental influence. Effective remote parenting, maintained through emotional support and clear boundaries, can successfully sustain a child's academic drive. Consequently, these results provide vital insights for migrant families and schools on how effective communication and structured caregiving can mitigate the potential negative consequences of parental absence.